Radiodocumentário “sustentabilidade na pesca em Parintins (AM)”: regulamentar ou não o acordo? - Albuquerque, Adria Helena Xavier (Brasil, 2023)
This report focuses on the research and production of a rádio documentary on the sustainability of fishing in the municipality of Parintins, whose general objective was to create a rádio documentary in order to discuss the promotion of sustainable fishing in Parintins (AM). The choice was made in view of the environmental impacts suffered in rural communities in the municipality of Parintins, reaching the general population, so it starts with the idea of passing on, through the product in audiojournalistic format, relevant information in the search for changes aligned by rural communities, through these mobilizations and understanding of supervisory organizations. In the theoretical foundation, fishing in the Amazon is highlighted with its historical process in the face of the means of degradation reaching municipalities such as Parintins and, more specifically, the daily life of rural communities. Therefore, the radio documentary has didactic material to raise awareness of the importance of applicable laws aligned with community mobilizations with awareness and sustainability.